Contributions to accounting and finance : essays in honour of professor Paavo Yli-Olli - Rothovius, Timo; Nikkinen, Jussi; fi=Vaasan yliopisto|en=University of Vaasa| (Vaasan yliopisto, 2007)
Kohdehenkilö: Yli-Olli, Paavo, 1947-2010 Kirjoittajat: Booth G.Geoffrey, Gurun Umit G., Högholm Kenneth, Sundkvist Kim, Ittonen Kim, Jokipii Annukka, Laitinen Teija, Järvenpää Marko, Kallunki Jukka.Pekka, Sahlström Petri, Äijö Janne, Laitinen Erkki K., Lehtonen Asko, nikkinen Jussi, Pynnönen Seppo, Rothovius Timo, Sihvonen Jukka, Vähämaa Sami, Suvas Arto, Takala Josu, Hirvelä Harkko, Liu Yang, Malindžák Dušan, Vieru Markku, Schadewitz Hannu fi=vertaisarvioitu|en=peerReviewed|